The COURAGE Built Environment Outdoor Checklist: An Objective Built Environment Instrument to Investigate the Impact of the Environment on Health and Disability. (29th July 2013) - Quintas, Rui; Raggi, Alberto; Bucciarelli, Paola; Franco, Maria Grazia; Andreotti, Alessandra; Caballero, Francisco Félix; Olaya, Beatriz; Chatterji, Somnath; Galas, Aleksander; Meriläinen‐Porras, Satu; Frisoni, Giovanni; Russo, Emanuela; et al.
<x xml:space="preserve">Abstract</x> A tool to assess the built environment, which takes into account issues of disability, accessibility and the need for data comparable across countries and populations, is much needed. The Collaborative Research on Ageing in Europe (COURAGE) in Europe Built Environment Outdoor Checklist (CBE‐OUT) helps us to understand when features of the neighbourhood environment have either a positive or negative impact on the accessibility of neighbourhoods for healthy ageing. The CBE‐OUT is composed of 128 items that can be recorded when present in the evaluated environment. Audits were performed in households randomly selected from each cluster of the sample for Finland, Poland and Spain, following precise rules defined by experts. Global scores were computed both section by section and in the overall checklist, rescaling the resulting scores from 0 (negative environment) to 100 (positive). The total number of completed CBE‐OUT checklists was 2452 (Finland, 245; Poland, 972; and Spain, 1235). Mean global score for our sample is 49.3, suggesting an environment composed both of facilitating and hindering features. Significant differences were observed in the built environment features of the three countries and in particular between Finland and the other two. The assessment of features of built environment is crucial when thinking about ageing and enhanced participation. The COURAGE in Europe project developed this tool to collect information on built environment in an objective evaluation of environmental features and is a recommended methodology for future studies. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message The CBE‐OUT checklist is an objective evaluation of the built environment and is centred on technical measurement of features present in the environment and has its foundations in the concepts of disability and accessibility operating in the International Classification of Functioning, Disability and Health (ICF) model. The CBE‐OUT checklist can be analysed using both the total score and the single section score, allowing an evaluation of the facilitating or hindering role of the environment and is usable for predictive analysis of ageing trends. The CBE‐OUT checklist makes it possible to collect information about the built environment by means of an objective evaluation of environment features and is a recommended methodology for future studies about the built environment.